Respuesta :
Answer:
-6 =y
Step-by-step explanation:
12( 5 + 2y ) = 4y - (6 - 9y)
60 +24y = 4y -6 +9y
Combine like terms
60 +24y = 13y -6
Subtract 24y from each side
60+24y-24y = 13y-24y -6
60 = -11y -6
Add 6 to each side
60+6 = -11y-6+6
66 = -11y
Divide each side by -11
66/-11 = -11y/-11
-6 =y
Answer:
y = -6
Step-by-step explanation:
STEP 1: 12(5 + 2y) - distribute 12 through the parentheses which will give you
60 + 24y. (when there is a "-" in front of a expression in parentheses, change the sign of each term of the expression)
STEP 2: then collect the terms and do 60 + 24y = 4y - 6 + 9y which will give you 13y
STEP 3: then move the variable to the left hand side and change its sign = 60 + 24y - 13y = -6 . move constant to the right hand side and change its sign like so 24y - 13y = -6 - 60
STEP 4: 24y - 13y = -6 - 60 collect the terms and youll get 11y = -6 - 60 then calculate the difference 11y = -66
STEP 5: Divide both sides of the equation by 11. y = -6 and thats your answer